PENGARUH KEBIJAKAN HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA KULIAH DI STIE EKA PRASETYA MEDAN - BAMBANG SUTEJO (JURNAL ILMIAH KOHESI, 2019)
Student satisfaction is a very important aspect and needs to get special attention because the student satisfaction as adeciding for the existence and success of the college. The purpose of this research is to know how much the influence ofprice policy and quality of service (physical evidence (tangible), reliability, responsiveness (responsiveness), guarantee(assurance), empathy (Emphaty) to the satisfaction of students in the high School of Economic Sciences Eka PrasetyaMedan. The research method used in this study is a survey with a quantitative approach through descriptive analysis. Thepopulation in this study was 940 students of the High School economics of Eka Praseetya Medan with samples taken asmany as 90 people. The sampling technique used is Probability Sampling (Random Sample) with Simple Random Samplingtechnique. The results of this study indicate that in test F (simultaneous test) there is an influence of the entire free variablesignificantly against the variable tied to the value of Fcount is 7.405, with the value of Ftable of 2.21. (F count (7.405) >Ftable (2.21)) and the significant value is 0.000 < 0.05. Meanwhile, from the results of T Test (partial test), obtained the resultof service quality variable physical evidence (tangable) is 0.388, which is greater than the value of sig. 0.05 and Thitung(0.868) < tTabel (1.663), the variable reliability is 0.066 is greater than the value of sig. 0.05 and Thitung (1.861) > tTabel(1.663), the Response power variable (responsiveness) is 0.180, which is greater than the value of sig. 0.05 and Thitung(1.353) < tTabel (1.663), the assurance variable is 0.885 which is larger than the value of sig. 0.05 and Thitung (-0.145) <tTabel (1.663) and the empathy variable (emphaty) are 0.278 which is greater than the value of sig. 0.05 and Thitung (-1.093) < tTabel (1.663). Based on the results of the research, there are several recommendations needed to improve thesatisfaction of students, among which the campus continues to improve the quality of its services in terms of physicalfacilities and responsiveness, empathy and the standardization of Service assurance, then in making the price policy shouldconsider the background of the student's economic situation and the price policy of other campuses (competitors) and as anevaluation material should.